Numerical analysis of the effect of implant geometry to stress distributions of the three different commercial dental implant system - Topkaya, Tolga; Solmaz, Murat Yavuz; Dündar, Serkan; Eltas, Abubekir (Cumhuriyet University Faculty of Dentistry, 2015)
Objectives: The success of dental implants is related to the quality, quantity of local bones, implant design and surgical technique. Implant diameter and length are accepted as key factors. Present work focuses to investigate the effect of titanium implant geometry to stress distributions in implant system. Materials and Methods: For this purpose three different implant models which are currently being used in clinical cases constructed by using ANSYS Workbench 12.1. The stress distributions on components of implant system under static loadings were analyzed for all models. Results: The maximum stress values that occurred in all components happen in the case of loading in which the Nucleoss T-4 (Nucleoss, Turkiye) implant is used, but the occurred lowest stress values happen in the case of Fi loading in which Nobel Active (Nobel Biocare, Zurich, Switzerland) implant is used. In all models, the maximum tensions have occurred in the neck region of the implants. Conclusions: The crestal bone loss in the neck region of the implants reduced the long-term survival rate of implants.The length and the size of the implant are the two important factors in the stress distribution.
Keywords: Dental implant design; Finite element analysis; Stress distribution